Oscilação mecânica pontual na modulação do tônus muscular de crianças com espasticidade - Pol, Stéphani de (2018)
Spasticity is a motor condition present in 75 to 88% of children with Cerebral Palsy (CP). A form of treatment for this condition is called punctual mechanical oscillation (PO). The purpose of this study was experience two application protocols of PO and the magnitude of their effects. Were analyzed 7 children of both sexes, with clinical diagnosis of PC that presented spasticity in the brachial biceps muscle. The first intervention protocol 1 (Int1) consisted of the application of OP in the spastic muscle tendon and the second intervention protocol 2 (Int2), on the muscle belly of the antagonist to the spastic. As evaluation was used on the Modified Ashworth Scale (MAS) while being picked up by the signs of the Mechanomiography (MMG). Checking data was made after 1, 15, 30, 45 and 60 minutes of the interventions. They were processed by the MatLab ® software and were treated as non -parametric, such as the Friedmann and Wilcoxon tests. It was observed that in the Int1 protocol there was statistical significance in the post-intervention instants of 15, 30, 45 and 60 minutes when compared to the median value of the pre-intervention, already in the protocol of Int2 there was statistical significance only at the moment Post1 when compared with the instant Pre-intervention, when the evaluation by the EMA was analyzed. On the first protocol being Pre (2 ± 0), Post1 (1 ± 1,75), Post15 (0 ± 1,75), Post30 (0 ± 1), Post45 (1 ± 1) e Post60 (1 ± 1). On the second protocol Pre (2 ± 1), Post1 (0 ± 1), Post15 (1 ± 1,5), Post30 (1 ± 1), Post45 (1 ± 0,75) e Post60 (1 ± 0). On the other hand, the values found by MMG in both temporal and spectral domain did not follow a pattern (p> 0.05). A comparison between the protocols (muscle tendon or muscular belly) showed no statistical difference in all the characteristics (MAS, MMGMF and MMGRMS). However, PO was a therapeutic resource that presented the spasticity modality for up to 60 minutes after its application, PO could contribute as a tool for the treatment of spasticity.